Amplification method for crosstalk reduction in multi‐core fibre amplifier. Issue 2 (1st January 2013) - Ono, H.; Yamada, M.; Takenaga, K.; Matsuo, S.; Abe, Y.; Shikama, K.; Takahashi, T.
Abstract : Proposed is a multi‐core fibre amplification method that can reduce crosstalk, in which the optical amplified signals in two adjacent cores propagate in opposite directions. By employing the proposed method, confirmed is a crosstalk improvement of more than 4 dB using the outer six cores of a seven‐core erbium‐doped fibre.